Social development and social policy in Guinea: health and education 1958-1984 - Corrie, Elizabeth M. (1988)
Guinea, a former French colony, experienced an abrupt severing of relationships with the colonial power when President Sékou Touré rejected De Gaulle’s offer of becoming part of a French commonwealth of nations and opted for total independence instead. France withdrew all support, trade and personnel within a matter of days, and Sékou Touré attempted to develop this new nation along strongly independent and ideological lines. He made a verbal commitment to social development and evolved an ambitious programme to develop the health and education services.